2001
DOI: 10.2166/wst.2001.0043
|View full text |Cite
|
Sign up to set email alerts
|

Surface runoff pollution by cattle slurry and inorganic fertilizer spreading: chemical oxygen demand, ortho-phosphates, and electrical conductivity levels for different buffer strip lengths

Abstract: As a way of dealing with the removal of pollutants from farming practices generated wastewater in the EU, we investigate the effect of spreading cattle slurry and inorganic fertiliser on 8 x 5 m2 and 8 x 3 m2 areas, referred to surface runoff chemical oxygen demand (COD), ortho-phosphates (o-P) and electrical conductivity (EC) levels, and the efficiency of grass buffer strips of various lengths in removing pollutants from runoff. The experimental plot was a 15% sloped Lolium perenne pasture. Surface runoff was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This result is in agreement with the findings of Borin et al [19], which showed that these particles are too small to be trapped in the buffer zone. Another study, however, shows that in a buffer zone with 15% slope the RE was equal to 90% for EC [18].…”
Section: Width Effect On Surface Runoff Qualitymentioning
confidence: 88%
See 2 more Smart Citations
“…This result is in agreement with the findings of Borin et al [19], which showed that these particles are too small to be trapped in the buffer zone. Another study, however, shows that in a buffer zone with 15% slope the RE was equal to 90% for EC [18].…”
Section: Width Effect On Surface Runoff Qualitymentioning
confidence: 88%
“…In addition, Uusi-Kämppä and Jauhiainen [17] studied the 10 m grass buffer zone with 12-18% slope and the 50% TS retention of the surface runoff under natural rainfall. Núñez-Delgado et al [18] estimated more than 90% RE for EC under simulated rainfall and an 8 m grass buffer zone with 15% slope. A study, conducted in a vegetative buffer zone with 5 m width and a row of trees with 1 m width, showed a 20% reduction in the EC of subsurface runoff [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation